2023
DOI: 10.3390/vaccines11030670
|View full text |Cite
|
Sign up to set email alerts
|

BMI-Associated Anti-Apolipoprotein A-1 Positivity in Healthy Adults after mRNA-Vaccination against COVID-19

Abstract: Elevated anti-apolipoprotein A-1 (AAA1) antibody levels associated with cardiovascular risk have been observed in previously SARS-CoV-2-infected or COVID-19-vaccinated individuals. Since patient safety is generally a priority in vaccination, we sought to investigate AAA1 antibody levels in healthy adults after mRNA vaccination. We conducted a prospective cohort study in healthy adult volunteers recruited from military workers of the Transport Air Base in Prague who had received two doses of mRNA vaccines. Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In particular, it has been established that immunoglobulins G to APOA1 serve as independent biomarkers for cardiovascular diseases and mortality, displaying proinflammatory and proatherogenic functions both in vivo and in vitro ( 33 , 34 ). The significant presence of autoantibodies against native and lipid-free apoA1 was demonstrated after two consecutive injections of anti-SARS-CoV-2 mRNA vaccines ( 35 ). A study on the general population showed that exposure to SARS-CoV-2 elevated baseline levels of anti-apoA-1 IgG ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been established that immunoglobulins G to APOA1 serve as independent biomarkers for cardiovascular diseases and mortality, displaying proinflammatory and proatherogenic functions both in vivo and in vitro ( 33 , 34 ). The significant presence of autoantibodies against native and lipid-free apoA1 was demonstrated after two consecutive injections of anti-SARS-CoV-2 mRNA vaccines ( 35 ). A study on the general population showed that exposure to SARS-CoV-2 elevated baseline levels of anti-apoA-1 IgG ( 33 ).…”
Section: Introductionmentioning
confidence: 99%